Pengaruh Pupuk Organonitrofos dan Volume Irigasi Terhadap Pertumbuhan Mint (Mentha piperita L.) Organik - Triyono, Sugeng; Marisa, Marisa; Haryanto, Agus (Jurnal Agricultural Biosystem Engineering, 2023)
Mint (Mentha piperita L.) is one of the aromatic herbs. The aim of this research was to investigate the effect of organonitrophos (organic fertizer) and irrigation water volume on the growth and yield of organically cultivated mint. The experiment was conducted in a completely randomized design (CRD) with two factors, namely the dose of organonitrophos consisting of 4 levels: D0 (0%), D1 (10%), D2 (30%), and D3 (50%) of the total weight of the media, and irrigation volume consisting of I1 (20-40%), I2 (50-70%), and I3 (80-100%) of the field capacity. The results showed that the dose of organonitrophos fertilizer and irrigation water volume affected the growth and yield of mint. The treatment that statistically produced the highest oven-dried weight (18.67 grams per plant) was D3I2 (50% compost fertilizer and 50-70% irrigation water). The treatment that produced the highest fresh weight (104.7 grams per plant) and was the most efficient was D2I1 (30% compost dose and 20-40% irrigation water). However, as a consequence, the choice of D2I1 significantly reduced the weight of oven-dried yield to 13.33 grams per plant.  Keywords: Organic, Mentha, Piperita, Organonitrofos, Irrigation